Edukasi Mengenai Gangguan Kognitif Pada Pasien Hipertensi di Poli Neurologi Rumah Sakit Universitas Mataram - Briliansy Briliansy; Herpan Syafii Harahap; Ilsa Hunaifi; Muhammad Ghalvan Sahidu; Stephanie Elizabeth Gunawan; Ni Nyoman Ayu Susilawati; Safat Wahyudi; Baiq Hilya Kholida; Diayanti Tenti Lestari; Setyawati Asih Putri (Universitas Mataram, 2023)
Cognitive impairment in hypertensive patients is a significant clinical problem. It is a prevalent condition that has a major impact on quality of life. Hypertension, characterized by persistently elevated blood pressure, has been identified as a potential risk factor for cognitive impairment. Assessing cognitive function in hypertensive patients is essential for early detection and intervention. Community participation is crucial to raise awareness about the symptoms of cognitive impairment in hypertensive patients. Therefore, education on cognitive impairment associated with hypertension is necessary to reduce its morbidity. This community service activity aims to provide education on the definition, signs, and symptoms, as well as early detection methods of cognitive impairment in hypertensive patients to patients and their families at the neurology clinic University of Mataram Hospital. The activity was conducted using an interactive method with the aid of PowerPoint slides. The participants were given a pre-test, followed by a presentation on the disease, a discussion session, and finally, a post-test. There were 14 participants in total. The education session began with a pre-test consisting of five questions about cognitive impairment and hypertension. The participants' average score was 74.2. The material covered definitions, symptoms, early signs, and how to conduct early detection of cognitive impairment and hypertension. The education session concluded with a post-test, which revealed that 10 participants (71.4%) showed an increase in their knowledge scores, with a mean score of 88.5. Effective communication, information, and education are essential in improving knowledge about the early detection of cognitive impairment in hypertensive patients.